1976
DOI: 10.1152/jappl.1976.40.4.508
|View full text |Cite
|
Sign up to set email alerts
|

Elastic constants of inflated lobes of dog lungs

Abstract: The elastic constants of dog lungs were determined at various degrees of inflation. In one set of experiments, the lobes were subjected to deformations that approximated the conditions of uniaxial loading. These data, together with the bulk modulus data obtained from the local slope of the pressure-volume curve, were used to determine the two elastic moduli that are needed to describe small nonuniform deformations about an initial state of uniform inflation. The bulk modulus was approximately 4 times the infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
134
3

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 0 publications
8
134
3
Order By: Relevance
“…These limitations are common to all measurements made in lung tissue strips 18 . Notably, however, the median stiffness measured in the parenchyma of normal lung tissue (shear modulus ~0.5kPa) does not differ substantially from estimates based on punch-indentation of intact lungs at resting volumes 19,20 . While lung tissue is known to exhibit non-linear stiffening with increasing deformation, it is not possible to test in a rigorous fashion whether this property persists down to the micro-scale with the methods employed here.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…These limitations are common to all measurements made in lung tissue strips 18 . Notably, however, the median stiffness measured in the parenchyma of normal lung tissue (shear modulus ~0.5kPa) does not differ substantially from estimates based on punch-indentation of intact lungs at resting volumes 19,20 . While lung tissue is known to exhibit non-linear stiffening with increasing deformation, it is not possible to test in a rigorous fashion whether this property persists down to the micro-scale with the methods employed here.…”
Section: Discussionmentioning
confidence: 63%
“…The lung has traditionally been mechanically characterized non-invasively, for instance using pressure-volume analysis 17 or punch-indentation of whole lungs 19,20 . Invasive methods such as the one described here alter the lung architecture in important ways through the loss of the air-liquid interface that normally exists in the air-filled lung and the loss of pre-stress that maintains lung partial inflation upon relaxation of respiratory muscles.…”
Section: Discussionmentioning
confidence: 99%
“…To study the uniaxial response of spongy lung, Lai-Fook et al [30] inflated lobes to a preset pressure, and then compressed these lobes between a pair of parallel platens while holding the alveolar pressure constant during the compression loading cycle. This is a significantly different experiment from those just discussed; it has a history effect.…”
Section: Inflation/compressionmentioning
confidence: 99%
“…Our observation that the cardiac fossa of the adult lung was less distortable than the lateral surface is consistent with that of Nagao (1973) who showed that the pleura isolated from the cardiac fossa is significantly less compliant than the pleura isolated from the lateral surface of the lung. The reduced distortability of the cardiac fossa may also reflect the pleura acting as a stretched membrane on the surface of the parenchyma (Lai-Fook et al 1976). The localised forces we applied to the concave cardiac fossa would further stretch the pleura, while similar forces applied to the convex lateral surface would reduce the stretch placed on the pleura.…”
Section: Discussionmentioning
confidence: 99%
“…How lung distortability changes in response to forces applied over a larger surface area, such as the left or right ventricle in situ, is not certain. Given that the tension of the pleural membrane increases with lung size (Hajji et al 1979) and given that lung deformations are influenced less by the pleura when the force is applied over a larger area (Lai-Fook et al 1976), developmental changes in lung parenchyma and changes in the size of the heart may influence this interaction. Although we applied force over a much smaller area (1 cm 2 ) than would be the case in vivo, the depths of the distortions we observed are nonetheless in keeping with those that might be expected in vivo.…”
Section: Discussionmentioning
confidence: 99%